Religious Identity and Plurality amongst Australian Catholics: Inclusions, Exclusions and Tensions - Souza, M. de (Journal for the study of religion, 2014)
In recent years, the Catholic Education Offices in the State of Victoria, Australia, have collaborated on a large research project with the Catholic University in Leuven that focuses on Catholic Identity. This is an interesting situation when there are, indeed, multiple Catholic identities evident in Australian society. This article, discusses the fluid and changing multicultural context that has shaped Australian Catholic identity by drawing on a variety of sources including research and statistical data, content analysis as well as snapshots of the lived experience of Australian Catholics from different backgrounds. The discussion will raise the question about a possible colonization of Catholic identity when a specific Catholic identity in a community is preferred while ignoring pluralistic identities in that community. The discussion will also attempt to offer some insights into the significant role that identity may or may not have in a pluralistic climate and its relevance for religious education.Keywords: interspiritual religious education, colonization of Catholic Identity, religious identity